O papel de biofilmes microbianos na osteoquimionecrose do osso mandibular induzida por ácido zoledrônico - Coelho, Camila Carvalho de Oliveira (2019)
Bisphosphonates-Related Osteonecrosis of Jaw (BRONJ) has no defined pathophysiology, but it is believed that local infection may participates of it development. The aim of this study was to evaluate the role of microorganism in osteochemonecrosis of jaw induced by zoledronic acid (ZA). For this purpose, C57BL/6 wild type mice (WT), specific-pathogen-free (SPF) and conventionalized (CONV), that are SPF animals inoculated with microbiota from WT animals (n = 6) were subjected to ZA adminstrations (1 mg/kg, intraperitoneally) for three weeks. Four weeks later, second lower left molar was extracted, followed by a new administration ZA realized seven days after surgery. Other animals, WT, SPF and CONV (n = 6) received saline solution intraperitoneally (controls). Body weight gain was performed weekly and haematological analyzes on day 0 and 70. Oral biofilms were collected from animals on days 0 and 70 for qualitative cytological analysis. After euthanasia (day 70), jaws and organs were excised. With the jaws, microtomographies was made to measure suggestive hypodense area of necrosis and, after decalcification, histologic slides (hematoxylin-eosin) for histomorphometric analysis of the post-exodontia alveolus. Kidney, liver, spleen and stomach were analyzed histopathologically for toxicity parameters. Qualitative cytological analysis revealed success in the conventionalization, with permanence of the similar microbiota to the WT animals from day 0 to 70. The SPF-ZA group, which exhibited cocci on day 0, showed filamentous bacteria at the end of the experiment. Greater hypodense area was seen in the post-exodontia alveoli of ZA-treated animals compared to saline groups. Histomorphometrically, WT-ZA and CONVZA groups exhibited a greater number of inflammatory cells and total osteoclasts in the postextraction sites, compared to those treated with saline, in addition to more frequent bacterial colonies and bone sequestra. The administration of ZA was associated with the probable occurrence of anemic events, a tendency of reduction in the number of platelets and the vacuolization of tubular epithelium in the kidney. SPF animals exhibited delay in body weight gain. Thus, the presence of a pathogenic oral microbiota was related to the occurrence of BRONJ lesions in WT and CONV mice, while their absence revealed, only, temporal cicatricial delay, without classic signs of necrotic lesion.